2019
DOI: 10.17305/bjbms.2019.4235
|View full text |Cite
|
Sign up to set email alerts
|

The potential of metabolic and lipid profiling in inflammatory bowel diseases: a pilot study

Abstract: Inflammatory bowel diseases (IBDs) are conditions that still pose significant problems. A third of the patients are either misdiagnosed or a proper diagnosis of Crohn’s disease (CD) or ulcerative colitis (UC) cannot be made. We need new biomarkers, so that we can offer patients the best treatment and keep the disease in an inactive state for as long as possible. Alterations in metabolic profiles have been incriminated in the pathophysiology of IBD. The aim of the present study was to identify molecules that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
5
13
0
Order By: Relevance
“…Glutamate receptors affect intestinal function (visceral sensitivity and motility) and brain function (stress response, mood, and behavior), and are involved in the pathogenesis of IBD ( Baj et al, 2019 ). In addition, studies have shown that patients with IBD have significant changes in plasma lipid and metabolic profiles, most of which are the elevated contents of glycerophospholipids and linoleic acid ( Tefas et al, 2020 ); IBD disorders are also implicated in the metabolism of glycerophospholipids in the body ( Guan et al, 2020 ). SEA intervention changed the abundance of these IBD-related differential metabolites, suggesting that its anti-inflammatory mode of action was related to intestinal metabolites in mice with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate receptors affect intestinal function (visceral sensitivity and motility) and brain function (stress response, mood, and behavior), and are involved in the pathogenesis of IBD ( Baj et al, 2019 ). In addition, studies have shown that patients with IBD have significant changes in plasma lipid and metabolic profiles, most of which are the elevated contents of glycerophospholipids and linoleic acid ( Tefas et al, 2020 ); IBD disorders are also implicated in the metabolism of glycerophospholipids in the body ( Guan et al, 2020 ). SEA intervention changed the abundance of these IBD-related differential metabolites, suggesting that its anti-inflammatory mode of action was related to intestinal metabolites in mice with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, citrate is essential for carrying acetyl-CoA from mitochondria to the cytosol. The significant increase in circulating triglycerides, observed in several studies on IBD, can be considered further evidence ( Levy et al, 2000 ; Sappati Biyyani et al, 2010 ; Tefas et al, 2020 ). Beyond the role of succinate as an energy supplier, this amino acid is an inflammation mediator; it selectively binds to and activates the succinate receptor-1 (SUCNR1), which promotes pro-inflammatory signaling pathways ( Mills and O'Neill, 2014 ).…”
Section: Metabolomics In Ibd and Covid-19mentioning
confidence: 78%
“…Additionally, these primary bile acids were shown in previous studies to bind to the farnesoid X receptor, which is linked to the elevated immune response in IBD [ 42 ]. Cholesteryl esters have also been shown to be elevated in subjects with IBD, potentially explained by lipid mobilization or by increased intestinal permeability [ 43 ]. The amine group within this module is composed of N-acylethanolamines as well as sphingosine.…”
Section: Resultsmentioning
confidence: 99%